Teachers’ views about early childhood education (Ece) learners’ participation in sporting activities in Gweru urban primary schools - Zireva, Cathren (Midlands State University, 2020)
The study sought to find out teachers’ views about ECE learners’ participation in sporting activities with reference to Gweru urban primary schools. This study emphasized the role of teachers in teaching sporting activities. Teachers, nationally, regionally and globally indicated that sporting activities reduces ECE learners’ deviant behaviours. The same teachers indicated that sporting activities among ECE learners relieve stress, depression and anxiety. These teachers further indicated that a child who participates in sporting activities is more likely to be mentally sharp. In view of these teachers perceptions the researcher sought further prop teachers’ views about ECE learners’ participation in sporting activities from those of varying backgrounds. The literature that was explored covered views of teachers from national, regional and international perspectives. The literature pointed out that these teachers were of the view that sporting activities help ECE learners’ physical growth and mental sharpness. They further noted that sporting activities was hampered by some of the ECE teachers who lack knowledge and skills. However other teachers were of the view that sporting activities pose risks of injury and diseases to ECE learners. Data was collected and analysed using the descriptive research design. The respondents’ views were captured through the instrument of questionnaire. Data collected was presented in graphs, tables and charts. The information was analysed and discussed giving the full picture of the teachers’ views on the subject area under study. In pursuit of this study the researcher found out that there was inadequate equipment and facilities for ECE sporting activities in Mambo Ascot cluster. The study found out that there were challenges arising from the critical shortage of funds to source for equipment and facilities for ECE sporting activities. The study further found out that strategies such as provision of adequate funding, uniform government policy for all primary schools and talent identification were to be put in place to invigorate the teaching of ECE Sporting activities so that this would match the teaching efforts put in teaching other disciplines. The study further found out that Gweru urban primary schools would be afforded funding for resourcing ECE Sporting activities. Teachers in these schools should undergo refresher courses so as to improve themselves in the teaching of this discipline. There is a need for these schools to forge a more realistic partnership with the communities to win their hearts so that they give them the necessary support in the teaching and upgrading of ECE sporting activities.